Evaluating Fertilizer Application Strategy for Improving Crop Yields and Reducing Mineral Nitrogen Leaching in High Rainfall Areas of Taiwan - Adhikari, Keshav R (Nepal Journal of Science and Technology, 2012)
A 2-yr pot experiment conducted on an upland sandy clay loam soil in National Taiwan University, Taipei evaluated crop yields and mineral nitrogen (Nmin) leaching as affected by fertilizer application strategy, viz., inorganic (100% N from urea), organic (100% N from compost), combined (compost plus urea) and a zero control (Ctrl) treatments. Cabbage (Brassica oleracea L.) and corn (Zea mays L.) were grown in annual rotation under simulated high rainfall conditions. The Nmin leaching was monitored adding 83 and 62 mm of water fortnightly to cabbage and corn respectively for a total of 28 times. One-way ANOVA was used to determine the statistical significance of treatment effect and Tukey test for means comparisons (p = 0.05). Treatment differences were subtle for dry matter yields (DMY) but the treatments were strikingly different for 2-yr cumulative Nmin leaching (6.66% in organic, 30.6% in inorganic and 8.10% in combined treatments). This difference was largely related to the ability of soil to an increased retention of added N under organic and combined fertilization treatments. Unlike reported elsewhere, N recoveries were relatively high in compost applied soils, with or without urea fertilizer application. It is concluded that framers’ practices of fertilization that has inherent problem of excessive N leaching in high rainfall areas of Taiwan could be improved by proper compost and urea combinations within agronomically recommended rate of N application. DOI: http://dx.doi.org/10.3126/njst.v12i0.6472 Nepal Journal of Science and Technology 12 (2011) 7-16